The Influence of the Project Based Learning Model Assisted by PhET Simulation on Students’ Critical Thinking and Problems Solving Abilities in Sound Wave Material - Dewa Ayu Dwik Dela Puspita; Aris Doyan; Hikmawati; Ahmad Harjono (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to test the effect of the Project Based Learning model assisted by PhET simulations on students' critical thinking and problems solving abilities in sound wave material. The type of research used was a Quasi experiment with a pretest-posttest control group design. The population in this study were all students in class XI Science at SMAN 3 Mataram. The sampling technique used purposive sampling technique, so that XI IPA 1 was obtained as an experimental class which was given treatment using a Project Based Learning model assisted by PhET simulation and XI IPA 2 as a control class using a conventional model. The test instrument used is a description of 12 question items consisting of 7 question items to measure critical thinking abilities and 5 question items to measure problem solving abilities. The hypothesis test used in this research is one-way MANOVA. The results of the hypothesis test show that the significance value of 0.001 is less than 0.05, so H_0 is rejected and H_a is accepted. Based on these results, it was concluded that there was an influence of the Project Based Learning model assisted by PhET simulations on students' critical thinking and problems solving abilities in sound wave material.